2009
DOI: 10.1359/jbmr.081208
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose, Randomized, Double-Blind, Placebo-Controlled Study of ACE-011 (ActRIIA-IgG1) in Postmenopausal Women

Abstract: The effects of ACE-011 on safety, pharmacokinetics, and bone biomarkers were evaluated in healthy, postmenopausal women. Our data indicate that ACE-011 results in a sustained increase in biomarkers of bone formation and reduction in markers of bone resorption. The activin type IIA receptor (ActRIIA) is the high-affinity receptor for activin. ACE-011 is a dimeric fusion protein consisting of the extracellular domain of the human ActRIIA linked to the Fc portion of human IgG1. ACE-011 binds to activin, preventin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(125 citation statements)
references
References 45 publications
5
117
0
3
Order By: Relevance
“…A phase I dose-escalation trial in healthy postmenopausal women showed dose-dependent increase in serum levels of bALP, persisting up to 120 days after a single intravenous injection of 3-mg/kg. Increase in serum levels of procollagen type I N-terminal propeptide (PINP, a marker of collagen deposition) was also observed, in contrast serum cross-linked C-telopeptide of type I collagen (CTX, a marker of bone resorption) levels were reduced by sotatercept [95]. Adverse events were mild and transient consisting of headache, toothache, infusion site reaction and infusion site hemorrhage.…”
Section: Treatment Of MM Bone Disease With Bone-anabolic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase I dose-escalation trial in healthy postmenopausal women showed dose-dependent increase in serum levels of bALP, persisting up to 120 days after a single intravenous injection of 3-mg/kg. Increase in serum levels of procollagen type I N-terminal propeptide (PINP, a marker of collagen deposition) was also observed, in contrast serum cross-linked C-telopeptide of type I collagen (CTX, a marker of bone resorption) levels were reduced by sotatercept [95]. Adverse events were mild and transient consisting of headache, toothache, infusion site reaction and infusion site hemorrhage.…”
Section: Treatment Of MM Bone Disease With Bone-anabolic Agentsmentioning
confidence: 99%
“…Adverse events were mild and transient consisting of headache, toothache, infusion site reaction and infusion site hemorrhage. Progressive and persistent hypertension was also observed in one patient due to a rapid and significant increase in hemoglobin levels at 1 week after administration of the second dose of sotatercept [95]. Given these promising results, the bone anabolic effects of sotatercept (ACE-011) have been assessed in 30 stage II/III MM patients with osteolytic lesions receiving standard chemotherapy, consisting of melphalan, prednisone and thalidomide (NCT00747123).…”
Section: Treatment Of MM Bone Disease With Bone-anabolic Agentsmentioning
confidence: 99%
“…A role for this gene in human erythropoiesis was found indirectly and serendipitously. The first clue came during a trial of a novel drug designed to treat osteoporosis, in which it was noted that the subjects developed an average of 12% rise in Hb [68]. This was unexpected and it quickly led to the hypothesis that this drug, sotatercept, could be used to treat anemia.…”
Section: Activin Receptor Ligand Trapsmentioning
confidence: 99%
“…Noteworthy, clinical trials performed with ActRIIFc ligand traps have revealed a number of considerable side effects (19,20), which likely would turn out to be devastating in the case of FOP. In this sense, administration of an activin A specific antibody may result to be more tolerable for patients.…”
Section: Anti-activin Based Therapies For Fopmentioning
confidence: 99%